Experimental Study of Almonertinib Crossing the Blood-Brain Barrier in EGFR-Mutant NSCLC Brain Metastasis and Spinal Cord Metastasis Models - Yuhan Zhang; Yaoshuai Zhang; Wenwen Niu; Xianming Ge; Fuhao Huang; Jinlong Pang; Xian Li; Yu Wang; Wei Gao; Fangtian Fan; Fangtian Fan; Shanshan Li; et al. (Frontiers Media S.A., 2021)
Roughly one third of non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI)-sensitive mutated (EGFRm) tumors experience disease progression through central nervous system (CNS) metastases during treatment. Although EGFR-TKIs have been reported to be favored in some patients with EGFRm NSCLC CNS metastases, novel EGFR-TKIs with proven efficacy in CNS pathologies are clinically needed.To investigate whether almonertinib, a novel third-generation EGFR-TKI for NSCLC, can cross the blood-brain barrier (BBB) and deliver treatment for EGFR-mutant NSCLC brain metastases and spinal cord metastases, we constructed NSCLC brain metastasis and spinal cord metastasis models in vivo to observe the anti-tumor effects of almonertinib. Using ABCB1-MDCK and BCRP-MDCK monolayer cells as the in vitro study model, the effects of transport time and drug concentration on the apparent permeability coefficient of almonertinib and its active metabolite, HAS-719, were investigated. The results of this study show that almonertinib can significantly inhibit PC9 brain and spinal cord metastases. Pharmacokinetic studies in mice revealed that almonertinib has good BBB penetration ability, whereas the metabolite HAS-719 does not easily penetrate the BBB. Early clinical evidence of almonertinib activity in patients with EGFRm-advanced NSCLC and brain metastases has also been reported. In conclusion, almonertinib easily penetrates the BBB and inhibits advanced NSCLC brain and spinal cord metastases.